Synthesis and Evaluation of Antidepressant‐like Activity of Some 4‐Substituted 1‐(2‐methoxyphenyl)Piperazine Derivatives. (14th August 2014) - Waszkielewicz, Anna M.; Pytka, Karolina; Rapacz, Anna; Wełna, Elżbieta; Jarzyna, Monika; Satała, Grzegorz; Bojarski, Andrzej; Sapa, Jacek; Żmudzki, Paweł; Filipek, Barbara; Marona, Henryk
<x xml:space="preserve">Abstract</x> A series of new derivatives of N‐(2‐methoxyphenyl)piperazine have been synthesized for their affinity toward serotonergic receptors and for their potential antidepressant‐like activity. They have been evaluated toward receptors 5‐HT1A, 5‐HT6, and 5‐HT7, as well as in vivo in the tail suspension, locomotor activity, and motor co‐ordination tests. All the tested compounds proved very good affinities toward 5‐HT1A and 5‐HT7 receptors. The most promising compound was 1‐[(2‐chloro‐6‐methylphenoxy)ethoxyethyl]‐4‐(2‐methoxyphenyl)piperazine hydrochloride, exhibiting affinity toward receptors Ki <1 nm (5‐HT1A) and Ki = 34 nm (5‐HT7). Antidepressant‐like activity (tail suspension test) was observed at 2.5 mg/kg b.w. (mice, i.p.), and the effect was stronger than that observed for imipramine (5 mg/kg b.w.). Sedative activity was observed at ED50 (locomotor test, mice, i.p.) = 17.5 mg/kg b.w. and neurotoxicity was observed at TD50 (rotarod, mice, i.p.) = 53.2 mg/kg b.w.